ANALISIS STRATEGI PENGEMBANGAN KAMPUNG KEREN (KREATIF DAN INDEPENDEN) BERBASIS BUDAYA LOKAL SEBAGAI PROGRAM UNGGULAN PEMERINTAH KOTA KEDIRI MENUJU PARIWISATA PERKOTAAN - Andy Bahtiar Nuril Huda; Eka Askafi (Universitas Islam Kadiri, 2021)
The government provides more effective and efficient public services in the context of accelerating regional economic development through vision and mission, superior programs and activities directed at developing local potential according to the characteristics of the basic needs of the local community by taking into account the available resources that can be used as a mainstay sector to attract tourists from outside the area. The local government of Kediri City supports this effort with the flagship program of Kampung Keren (Creative and Independent). The research was carried out in the Kampung Dalem Village, Kediri City with the objectives of the research being (1) analyzing the types of regional superior product potential based on the type of marketing product entity, stakeholder participation, and marketing strategies in the Kampung Keren clusters, (2) analyzing the barriers to potential product development superior areas supporting the Kampung Keren clusters, (3) analyzing the causes of obstacles to the development of potential superior products from the areas supporting the Kampung Keren clusters, (4) analyzing SWOT-QSPM-based development strategies for regional superior products based on Kampung Keren clusters. The methodology is descriptive and the data is collected through discussion, documentation, and direct observation with 30 informants or respondents. The results of the study are 50 (fifty) potential local products that can be developed to support urban tourism based on the Kampung Keren cluster with various types of marketing product entities, especially services, with the largest community participation, and the level of promotion that must be more varied. The obstacles are especially in terms of limited budget and the main cause of the COVID-19 pandemic which requires the government to reallocate the budget for the development of Kampung Keren for prevention, handling and recovery of the economic impact of the COVID-19 pandemic. government stakeholders, entrepreneurs, citizens, media, academics, in providing participation in goods, money, thoughts, expertise, personnel.